Endovascular Treatment of a Gastroduodenal Artery Pseudoaneurysm Rupture after a Car Accident - Sofia Dutra; Filipe Veloso Gomes; Tiago Bilhim; Élia Coimbra (Acta Médica Portuguesa, 2017)
The authors present a case of a 39-year-old man with alcoholic chronic pancreatitis that was admitted in the emergency department after a car accident, complaining of abdominal pain and looking pale. The patient was hemodinamically unstable, requiring blood transfusions. He underwent computed tomography angiogram of the abdomen and pelvis, showing a pseudoaneurysm of the gastroduodenal artery and a hemoperitoneum. He was referred to our interventional radiology unit and submitted to endovascular treatment, consisting of ‘backdoor’ and ‘frontdoor’ embolization of the gastroduodenal artery and pseudoaneurysm neck with coils, with total exclusion in control angiography. With this case description we intend to highlight the rarity of the pseudoaneurysm rupture of the gastroduodenal artery and to emphasize the importance of an interventional radiology response that had a fundamental role in the endovascular treatment, in an emergency context.